(3aGYdjI HQfGeL CfTWI bGFe Ydi GdhSGFW GdeJYOOI dYdGL GVWQGHGJ GddZI dOi YjfI ef GdeYGbjf YbdjG GdbGHdjf ddJYdje (B/ s - (3eMeO CMeO CMeO EHQGgje NVjQs; (3TMGJg SdjeGf eMeO SdjeGf (B: s; (3aGWeI GdRgQGA eLOi YHOGdSejY (B: s ((3GdbGgQI (B: s (3eMeO CMeO CMeO EHQGgje NVjQ (B: s, 2021)
(3jgOa GdHMK Edi(B: (3YdGL GdGVWQGHGJ GddZhjI dOi GdCWaGd GdeYGbjf YbdjG HGSJNOGe HQfGeL bGFe Ydi GdhSGFW GdeJYOOI(B. (3h GdJMbb ef aGYdjI HQfGeL HGSJNOGe GdhSGFW GdeJYOOI dJMSjf eSJhi GdCOGA GddZhi dOi YjfI ef GdCWaGd GdeYGbjf YbdjG GdbGHdjf ddJYde h GdJMbb ef GSJeQGQjJg(B: (3h GYJeO Ydi YjfI ef GdCWaGd GdeYGbjf YbdjkG GdbGHdjf ddJYde(B. (3h CYJeO Ydi YjfI echfI ef (B(10) (3CWaGd ef GdCWaGd GdeYGbjf YbdjG GdbGHdjf ddJYde eef JJQGhM CYeGQge Hjf (B(7-12) (3SfI GdPjf dOjge GVWQGHGJ ai GddZI HeYgO GdJQHjI GdacQjI HGdLjRI(B. (3h GSJNOe GdHMK GdefgL THg GdJLQjHj h GdJUeje GdJLQjHj Ph GdeLehYI GdhGMOI MjK Cfg jJeGTi eY WHjYI GdHMK GdMGdi(B. (3ceG GYJeO GdHMK Ydi GdCOhGJ GdJGdjI(B: (3GdeUahaGJ GdedhfI d`` (B"(3QGaf(B" ((3JQLeI(B: (3YeGO CMeO(B): (3h ebjGS GddZI GdeYOd (B((3EYOGO(B: (3fgdI GdQaGYi(B: 2011). (3h GdHQfGeL GdbGFe Ydi GSJNOGe GdhSGFW GdeJYOOI dJNaja MOI GdGVWQGHGJ GddZhjI ddCWaGd GdeYGbjf YbdjG GdbGHdjf ddJYdje(B. (3h CSaQJ fJGFL GdHMK Yf(B: (3hLhO aQhb PGJ OdGdg EMUGFjI Hjf eJhSWi QJH OQLGJ GdCWaGd GdeYGbjf YbdjG GdbGHdjf ddJYdje HGdeLehYI GdJLQjHjI Ydi ebjGS GddZI GdeYOd ai GdbjGSjf GdbHdi h GdHYOi dJWHjb GdHQfGeL dUGdM GdbjGS GdHYOi(B: (3h YOe hLhO aQhb PGJ OdGdg EMUGFjI Hjf eJhSWi QJH OQLGJ GdCWaGd GdeYGbjf YbdjG GdbGHdjf ddJYdje HGdeLehYI GdJLQjHjI Ydi ebjGS GddZI GdeYOd ai GdbjGSjf GdHYOi h GdJJHYi dJWHjb GdHQfGeL HYO eQhQ TgQ Ydi GdbjGS GdHYOis
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI ddWahdI GdeHcQI (B- (3bSe GdYdhe GdfaSjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdGVWQGHGJ GddZhjIs; (3GdCWaGd GdeYGbjf YbdjG GdbGHdjf ddJYdjes; (3GdhSGFW GdeJYOOIs